Design Discourse Composing and Revising Programs in Professional and Technical Writing - Franke, David; Reid, Alex; Di Renzo, Anthony (Open textbook library., 2010)
Design Discourse: Composing and Revising Programs in Professional and Technical Writing, edited byDavid Franke, Alex Reid, andAnthony Di Renzo,addresses the complexities of developing professional and technical writing programs. The essays in the collection offer reflections on efforts to bridge two cultures — what the editors characterize as the "art and science of writing" — often by addressing explicitly the tensions between them. Design Discourse offers insights into the high-stakes decisions made by program designers as they seek to "function at the intersection of the practical and the abstract, the human and the technical."